P Android-Based Monitoring and Control of Electricity Consumption: Android-Based Monitoring and Control of Electricity Consumption - Rahmat Azyad Samallo; Septi Andryana; Ratih Titi Komala Sari (Institute of Computer Science (IOCS), 2020)
The purpose of this study is to create a system of